Writing UX requirements in acceptance criteria: extended version of a case study in startups - Jonathan Souza; Luciana Zaina (CLEI Electronic Journal)
User experience (UX) is a topic widely discussed in the software industry. The elaboration of UX requirements is an activity that practitioners face difficulties during the software specification. On the other hand, user stories (US) are a well-known artifacts to describe software requirements. Frequently, acceptance criteria (AC) complement the US specification by giving more details about the require-ment scope, functionality, and quality requirements of the software. Taking into account US/AC relevance, ACUX (Acceptance Criteria of User eXperience) guide was proposed to support software teams to the writing of UX requirements during the elaboration of AC. In this paper, a case study carried out with software teams from two startups investigated the use of ACUX. The study aims to ob-serve the changes that the guide adoption employed in the teams’ routine concer-ned on UX requirements elaboration. The findings revealed that ACUX im-proved team communication and played the role of a reminder for the developers memory about the relevant aspects of UX to be considered in the requirement specification.